2018
DOI: 10.1186/s12955-018-0881-3
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre cross-sectional clinical evaluation study about quality of life in adults with disorders/differences of sex development (DSD) compared to country specific reference populations (dsd-LIFE)

Abstract: BackgroundPrevious studies in quality of life (QOL) in individuals with disorders/differences of sex development (DSD) have been restricted to subpopulations of the condition. We describe QOL in adult persons with DSD compared to country specific references and assess the impact of diagnosis.MethodsThe multicentre cross-sectional clinical evaluation (dsd-LIFE) took place in 14 specialized clinics in six European countries. Adolescents (≥16 years) and adults having a DSD condition were included from 02/2014 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 29 publications
(66 reference statements)
1
34
2
Order By: Relevance
“…In another report on the dsd-LIFE data, the authors found that shame, stigma, low self-esteem, and low satisfaction with healthcare were associated with clinically significant symptoms of depression and anxiety [33]. Finally, a study on quality of life among dsd-LIFE participants found that good self-reported health status was the most important predictor of psychological quality of life; the authors concluded that providing good physical and mental health care to intersex people is likely to improve their quality of life [34]. In our intersex health study, we found that socio-demographic characteristics such as age and income inadequacy were significantly associated with mental health outcomes, similar to population trends [35].…”
Section: Plos Onementioning
confidence: 98%
“…In another report on the dsd-LIFE data, the authors found that shame, stigma, low self-esteem, and low satisfaction with healthcare were associated with clinically significant symptoms of depression and anxiety [33]. Finally, a study on quality of life among dsd-LIFE participants found that good self-reported health status was the most important predictor of psychological quality of life; the authors concluded that providing good physical and mental health care to intersex people is likely to improve their quality of life [34]. In our intersex health study, we found that socio-demographic characteristics such as age and income inadequacy were significantly associated with mental health outcomes, similar to population trends [35].…”
Section: Plos Onementioning
confidence: 98%
“…Other than in this study, all or the majority of patients with CAH included in QoL studies have had the classical phenotype. The reports are inconsistent and indicate varying degrees of impaired QoL (18,170,171,172,173,174). The outcome of genital surgery and satisfaction with sexual function affect the general wellbeing and are likely to affect the QoL of women with classic CAH, especially women with the null and I2 splice genotypes (175,176).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Physical or mental health problems are highly prevalent in individuals who have a DSD (2,8). Importantly, not the specific diagnosis but the personal health status predicts QoL (4). Overall, individuals with a DSD report good QoL but studies are often contradictory, possibly due to differences in local treatment and care, age and cultural context and differences in methodology.…”
Section: Psychosocial Fieldsmentioning
confidence: 99%
“…The prevalence of the individual conditions is mostly very low and only a small fraction of all conditions characterised by variations in sex characteristics pose major clinical challenges and/or require multidisciplinary care (1). Recent outcome studies suggest that having a DSD may impact an individuals' health status and psychological well-being in every stage of life (2,3,4), though physical or psychological comorbidities have been rarely studied in detail, especially in adults. Influencing factors include the rarity of the respective conditions, individual drawbacks to participate in medical studies and the dispersion of affected individuals over decentralised health care structures, with frequent loss of patients for follow-up.…”
Section: Introductionmentioning
confidence: 99%